The role of oral traditions in internalizing smong wisdom: Perspectives from the Simeulue community - Ramli, Ramli; Gadeng, Ahmad Nubli; Azis, Daska; Yusuf, Yunisrina Qismullah; Razali, Razali (Indonesian Journal of Applied Linguistics, 2024)
This research aims to identify the oral tradition of internalizing smong wisdom, recognized as successful in saving the people of Simeulue, Aceh, Indonesia, during the 2004 tsunami disaster. It employs a qualitative approach with descriptive methods. Data collection techniques include in-depth interviews with 30 informants comprising traditional leaders and community members knowledgeable about smong local wisdom. Data analysis utilizes thematic analysis. The research findings reveal that the ancestors of the Simeulue people internalized smong local wisdom through oral culture, which held significant literary value since 1907. The internalization of smong wisdom is evident through its transmission across generations, reflected in the community's smong narrative during disasters and using mananga-nanga, manafi-nafi, and nandong as educational tools. Based on insights from the informants, including traditional leaders and community members, they affirmed the widespread practice and knowledge of smong wisdom across all age groups in Simeulue. They utilize mananga-nanga (lullabies) for infants under five years old, manafi-nafi (folktales) for the general public, and nandong (songs) at specific events of special conditions. The informants of this study believe that instilling the values of local wisdom from an early age fosters collective memory, which can be easily recalled and applied by future generations. This facilitates the efficient transfer of local wisdom values in line with the ancestors’ expectations. Internally, within local communities, internalization occurs traditionally through oral culture.